Cytotoxic Effects of Hydroxy Coumarin Derivatives on Mouse Neuroblastoma N2a Cell Line: Effects of Hydroxy Coumarin Derivations in N2A cell line - Sargolzaei, Javad; Sadeghian, Hamid; Golahmadi, Sanaz; Soukhtanloo, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2020)
Neuroblastoma is one of the nervous system cancers, which approximately consists of 9% of childhood cancers. In this study, we evaluated the toxic effects of prenyl hydroxy coumarin derivatives on apoptosis of the neuroblastoma cell line N2A. N2A cells were cultured in DMEM medium, then the effects of different concentrations (0.75–200 μg/mL) of prenyl hydroxy coumarin derivatives during 24, 48, and 72 h were studied. Cell viability was quantified by MTT assay; apoptotic cells were determined using PI staining of DNA fragmentation through flow cytometry (sub-G1 peak). The toxic effect of 3- farnesyl oxi coumarin in the N2A cell starts at 6.25 μg/ml and increases relatively depending on rising in concentration and over time. The toxicity and apoptosis of 3- farnesyl and 6- farnesyl oxi coumarin is more than 3- Geranyl and 6-Geranyl oxi coumarin. Prenyl hydroxy coumarin induces peak sub-G1 in flow cytometry compared to the control group, indicating that induced toxicity, which is involved in apoptotic cell death. Different concentrations of derivatives (0.75-200 μg/mL) in lymphocytes did not induce any anti-proliferative effect in 24 h. In conclusion, prenyl hydroxy coumarin derivatives induce apoptotic effects in the N2A cell line. Then prenyl hydroxy coumarin derivatives sound to be chemotherapeutic agents for the neuroblastoma cancer cells.